Burnout Experienced by Military Nurses: A Systematic Review. - Christiansen, Mollie F.; Taylor‐Clark, Tanekkia; Yoder, Linda H.; Kenny, Deborah (Worldviews on Evidence-Based Nursing (John Wiley & Sons, Inc.), 2026)
Background: Burnout is associated with adverse physical and psychological health outcomes in civilian nurses. Among military populations, these adverse health outcomes have the potential to degrade readiness at both individual and system levels. There are few scientific studies about burnout among military nurses. Aim: The purpose of this systematic review was to critically examine the evidence regarding the prevalence and individual characteristics associated with burnout among active‐duty military nurses. Methods: A systematic review was conducted using a comprehensive, iterative search. Peer‐reviewed reports of studies that included burnout in the stated aim or research question and used a validated instrument to measure burnout were included. Results: Five studies met inclusion criteria. The reported prevalence of burnout among military nurses was between 1.7% and 13.8%. Scoring, measurement, and operational definitions differed, so results should be interpreted with caution. Increased military and nursing experience, a higher volume of work hours, and working on non‐day shifts may contribute to burnout among military nurses. Differences in burnout based on sex and military versus civilian status are mixed. Linking Evidence to Action: Researchers should consider alternative theoretical frameworks and measurement instruments when studying burnout among military nurses. Inconsistency in measurement methods from previous studies limits current understanding. Military‐specific cultural concepts may play a role in mitigating burnout among military nurses. Trial Registration: CRD420251036405